Nocturnal light exposure stimulates the cardiac fibrinolysis system and stress responses in C3H/He mice. Issue 188 (April 2020) - Yasuda, Michiko T.; Watanabe, Yuto; Hosono, Takashi; Seki, Taiichiro; Suzuki, Taka-aki; Sakakibara, Hiroyuki; Shimoi, Kayoko
Graphical abstract: Unlabelled Image Highlights: Nocturnal light for 3 hrs increased murine cardiac PAI-1 gene and protein level in mice. TF was induced and tPA was down-regulated by temporal nocturnal light (250 lx). Nocturnal light induced plasma ACTH, corticosterone and adrenaline. Temporal nocturnal light exposure can act as a stressor for mice.